2003
DOI: 10.1093/jn/133.7.2125
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cyanidin 3-O-β-D-Glucoside-Rich Purple Corn Color Prevents Obesity and Ameliorates Hyperglycemia in Mice

Abstract: Anthocyanins, which are used as a food coloring, are widely distributed in human diets, suggesting that we ingest large amounts of anthocyanins from plant-based foods. Mice were fed control, cyanidin 3-glucoside-rich purple corn color (PCC), high fat (HF) or HF + PCC diet for 12 wk. Dietary PCC significantly suppressed the HF diet-induced increase in body weight gain, and white and brown adipose tissue weights. Feeding the HF diet markedly induced hypertrophy of the adipocytes in the epididymal white adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
549
0
21

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 773 publications
(588 citation statements)
references
References 25 publications
18
549
0
21
Order By: Relevance
“…Previous reports 23,24 have shown that supplementation of 320 mg day -1 kg -1 23 of C3G or 160 mg day -1 kg -1 24 of anthocyanins through the food pellets reduces fat accumulation in mice.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous reports 23,24 have shown that supplementation of 320 mg day -1 kg -1 23 of C3G or 160 mg day -1 kg -1 24 of anthocyanins through the food pellets reduces fat accumulation in mice.…”
Section: Discussionmentioning
confidence: 92%
“…It is noteworthy that blood oranges are characterized by a high content in anthocyanins, in particular C3G, reported to attenuate obesity and ameliorate insulin resistance when supplemented to HFD fed mice. 23 However, a large consumption of orange juice, despite its healthy effects, has the potential to contribute to overweight because of its sugar (10%B w/v), in particular fructose (B2.5%w/v) content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a previous study, obese mice fed a diet rich in cyanidin-3-glucoside from purple corn for 12 weeks have reduced body weight, as well as decreases in white and brown adipose tissue weights [100]. The study demonstrates that hyperglycemia, hyperinsulinemia, hyperleptinemia, and an increase in the tumor necrosis factor (TNF-a) mRNA level occurred in the obese rats are normalized when treated with purple corn diet.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 97%